Price Determinants of Emission Allowance: Stock Market and Economic Dynamics - Rani, Aliya Cisya; Wulandari Pangestuty, Farah (Contemporary Studies in Economic, Finance and Banking, 2026)
The European Union Emission Trading System (EU ETS) is oftentimes viewed as the foundational model for national-level air ETS, given its status as the earliest and most extensive carbon market globally. Throughout the years of its operation, the price of the European Union Allowance experienced an upward trend which reached its highest point in the first quarter of 2023 only to drop significantly the year after. Persistent volatility in the price of carbon poses a threat to the effectiveness of EU ETS in reducing emissions. This study builds upon the limitations in previous literature to examine the possible price determinants of EUA focusing on GDP growth, R&D expenditures, and Dow Jones Euro Stoxx 50. The employed Vector Autoregression (VAR) model reveals that GDP growth positively affects EUA prices with a delayed effect, while stock market movements respond to rather than drive carbon price changes. Although R&D spending shows no direct impact, it may indirectly influence prices through economic growth.